Exploring the intersection between AI technologies and media literacy in older adults: A systematic research review - Martín-Martín, Francisco Marcos; Aguaded Gómez, Ignacio (IJERI: International Journal of Educational Research and Innovation, 2025)
This paper presents a systematic review of research exploring the utilisation of artificial intelligence (AI) in the context of education and communication for older adults. In accordance with the PRISMA 2020 protocol, a total of 15 studies were selected from the WoS, Scopus, EBSCO, ERIC and Dialnet Plus databases, published between 2015 and 2024, for analysis. The findings indicate a paucity of scientific output in the field of educommunication pertaining to AI and older people, underscoring the necessity for an expansion of research in this domain. Potential avenues for future inquiry include the design of adaptive AI applications, the development of targeted media literacy programmes, and the creation of conversational agents to enhance the efficacy of educational intervention strategies with older people. However, the persistence of the digital divide and ageism impede the effective integration of AI.